2015
DOI: 10.3923/crb.2015.34.40
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility of Escherichia coli Isolated from some Drinking Water Sources in Tamale Metropolis of Ghana

Abstract: This is the first report on the antibiotic resistance of Escherichia coli isolated from drinking water samples in Tamale Metropolis of Ghana. Antibiotic susceptibility test was performed using the disc diffusion method and the results interpreted using the Clinical and Laboratory Standards Institute guidelines. A total of 56 water sample Escherichia coli isolates were screened against nine different antibiotics. Overall, 37.90% of the Escherichia coli isolates were resistant, 12.90% were intermediate and 49.21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
(32 reference statements)
4
7
0
Order By: Relevance
“…In India, E. coli isolated from the Ganga river showed resistance to antibiotics cephalosporin (37%), ampicillin (20%), amoxicillin (20%), tetracycline (20%), and ciprofloxacin (5.30%) (Biswas et al, 2015). Similarly, several studies had reported the presence of antibiotic-resistant E. coli in different environmental and clinical samples (Sayah et al, 2005;Ram et al, 2007Ram et al, , 2008Li et al, 2010;Tagoe et al, 2011;Guo et al, 2014Guo et al, , 2017Adzitey et al, 2015;Chen et al, 2017;Muringani, 2017;Amer et al, 2018;Diwan et al, 2018;Igwaran et al, 2018;Lu et al, 2018;Mishra et al, 2018;Mitali et al, 2018;Vital et al, 2018;Amador et al, 2019;Sandhu et al, 2019). Study on distribution of ARGs in the present study reflects that the spring water of Sikkim are reservoirs of multiple ARGs.…”
Section: Discussionmentioning
confidence: 92%
“…In India, E. coli isolated from the Ganga river showed resistance to antibiotics cephalosporin (37%), ampicillin (20%), amoxicillin (20%), tetracycline (20%), and ciprofloxacin (5.30%) (Biswas et al, 2015). Similarly, several studies had reported the presence of antibiotic-resistant E. coli in different environmental and clinical samples (Sayah et al, 2005;Ram et al, 2007Ram et al, , 2008Li et al, 2010;Tagoe et al, 2011;Guo et al, 2014Guo et al, , 2017Adzitey et al, 2015;Chen et al, 2017;Muringani, 2017;Amer et al, 2018;Diwan et al, 2018;Igwaran et al, 2018;Lu et al, 2018;Mishra et al, 2018;Mitali et al, 2018;Vital et al, 2018;Amador et al, 2019;Sandhu et al, 2019). Study on distribution of ARGs in the present study reflects that the spring water of Sikkim are reservoirs of multiple ARGs.…”
Section: Discussionmentioning
confidence: 92%
“…Water also helps to remove waste, lubricates joints, serve as a major component of blood, and a necessary medium for many chemical reactions that help in the formation of meat, eggs, and other animal and plant foods [4]. Potable water is expected to be odorless, tasteless, free from toxic substances, microbial and chemical contaminations [2,5]. Water is also known to be the dwelling place for most bacteria and other microorganisms which cause a variety of waterborne infections such as cholera, typhoid, bilharzia, and malaria [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Adzitey et al, 2015 studies E. coli isolated from drinking water and tap water at Livestock farm, incidence was found to be 60 % (5 out of 3) and 10% (3 out of 25) respectively while in our study E coli was isolated in 68.18% ( …”
Section: Discussionmentioning
confidence: 84%